Regulatory mechanisms and interactions of mitophagy and ketone body metabolism in cardiac metabolism - Shujun Ding; Yuna Hu; Qin Zhang; Xinyi Liu; Xuan Zhao; Yajing Zhao; Wen Zhang (Frontiers in Cardiovascular Medicine, 2026)
Cardiac function depends on tightly regulated energy metabolism, with mitochondria serving as key sites of cellular energy production. Mitophagy, a selective form of autophagy that maintains mitochondrial quality, has received growing attention for its role in cardiomyocyte metabolism. Under specific physiological and pathological conditions, the myocardium increases its use of ketone bodies as energy substrates, and ketone body metabolism is closely linked to mitochondrial function. However, the relationship between mitophagy and ketone body metabolism is incompletely understood, particularly in cardiovascular disease. This review summarizes their roles and regulatory mechanisms in the myocardium and evaluates evidence for a potential bidirectional relationship. Mitophagy may preserve the mitochondrial capacity required for ketone body oxidation, whereas ketone body metabolism and β -hydroxybutyrate-mediated signaling may regulate mitophagy and mitochondrial stress resilience. By integrating these interactions across cardiovascular disease phenotypes, this review highlights their potential therapeutic relevance and identifies priorities for mechanism-based intervention and clinical translation.